The Correlation between Body Mass Index, Physical Activity, and The Degree of Premenstrual Syndrome - Tarsisius Tas'au; Lewi Jutomo; Sarci Magdalena Toy; Rut Rosina Riwu (Lontar : Journal of Community Health, 2021)
Premenstrual syndrome is a collection of physical and psychological symptoms that appear 7 to 10 days before menstruation in women of childbearing age and disappear after menstruation. Premenstrual syndrome can be caused by body mass index and exercise activity. This is an analytic study with a cross-sectional study design that consists of 92 respondents as the sample was selected by simple random sampling. This research was conducted from September to October 2020. Data collection used interview techniques using a questionnaire and anthropometric measurements of body weight and height. Statistical analysis using the chi-square test. The results of the chi-square statistical test showed that body mass index (p-value = 0.041 ≤ 0.05) and sports activities (p-value = 0.010 ≤ 0.05) are related to the degree of premenstrual syndrome. It is important to maintain ideal body weight by consuming nutritious and healthy foods and balanced with regular exercise activities so that the body mass index is normal and avoids the problem of premenstrual syndrome and achieves optimal health.